RECENT PERIODICALS RELATING TO THEOLOGICAL STUDIES (The journal of theological studies, 1927)
RECENT PERIODICALS RELATING TO THEOLOGICAL STUDIES, The Journal of Theological Studies, Volume os-XXVIII, Issue April, 1 April 1927, Pages 335–336, https://doi.